Alternativas para extração de sais a partir de efluentes da indústria salineira sob diferentes condições de umidade e plasma atmosférico - Fontes, Kristy Emanuel Silva (Universidade Federal Rural do Semi-Árido, 2020)
Salt production data in the regions close to the city of Mossoró, in the state of Rio Grande do Norte - RN, show that around 2.5 m³ of effluent (bittern) is discarded for every 1 ton of salt produced. This effluent is rich in salts that can be extracted, composed of ions, such as: Na+1 , K +1, Ca+2 , Mg+2, Cl-1 and SO4 -2 . From this perspective, the present work sought to explore alternative routes for the recovery of salts by evaporation under controlled laboratory conditions. For this, the mother liquor was subjected to evaporation stimulated by a heating plate at 40 ° C. The influence of relative air humidity in 50 % (Ur 50 %) and 70 % (Ur 70 %) was investigated, in addition to the action of atmospheric cathodic plasma under 50 % relative humidity (Ur 50 % _P). During the evaporation, every 3 consecutive hours, the salts produced on the surface of the bittern (Flower of Salt - FS), the accumulated salts at the bottom of the container (Sedimented - Sed.) and 1 ml aliquots of the bittern (Concentred - Conc.), enabling mass and chemical analysis of recovered salts. It was found that morphological changes occurred in the FS obtained in the condition under plasma treatment, characterized by an increase in the density of nuclei and a reduction in the size of grains to values 96.74 % lower than those naturally generated. Considering the evaporation in different humidities, it was verified that in 70 % of humidity (Ur 70 %) there was a greater recovery of salts from the bittern through the FS (where it was possible to extract more Ca+2 than in the other conditions); in Ur 50 % condition more salts were recovered through Sed. (where more Na+1 and Mg+2 were extracted than in other conditions); and in the Ur 50 % _P condition, it was possible to stimulate both a greater recovery of salts by FS and Sed., composed of salts considerably richer in K+1 than in other conditions. The experiments, in the three conditions, were conducted during the evaporation of water from 1.235 g/cm³ to 1.261 g/cm³, in which quantities were compared such as average total volume evaporated, average acidification of the bittern and average conductivity of the solution
Keywords: Recuperação e caracterização de sais; Plasma atmosférico catódico em líquido; Flor de sal; Salinicultura; Recovery and characterization of salts; Atmospheric cathodic plasma in liquid; Flower of salt; Culture of salt production; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA